Soluble RAGE Plasma Levels in Patients with Coronary Artery Disease and Peripheral Artery Disease. (9th October 2013) - Falcone, Colomba; Bozzini, Sara; Guasti, Luigina; D'Angelo, Angela; Capettini, Anna Clizia; Paganini, Edoardo Maria; Falcone, Rossana; Moia, Roberto; Gazzaruso, Carmine; Pelissero, Gabriele
Abstract : The objective of the present study was define in a relatively large patient population with coronary artery disease (CAD) whether the concomitant presence of peripheral artery disease (PAD), which is known to convey additional cardiovascular risk, was associated with different circulating levels of sRAGE with respect to CAD alone and control subjects. Clinical and laboratory parameters including the ankle brachial index (ABI) and sRAGE (enzyme-linked immunosorbent assay kit) were investigated in 544 patients with angiographically documented CAD and 328 control subjects. 213/554 CAD patients (39%) showed an ABI <0.9 associated with typical symptoms (group CAD + PAD), whereas 331 patients were free from PAD. The concentration of plasma sRAGE was significantly lower (P < 0.0001 ) in CAD population, with and without PAD, than in control subjects. Among CAD patients, those with PAD showed lower levels of sRAGE. The distribution of the three groups (CAD, CAD + PAD, and controls) according to sRAGE tertiles showed that lower levels were more frequent in patients with CAD and CAD + PAD, whereas higher levels were more frequently found in controls. CAD patients presenting with PAD have lower sRAGE levels than CAD patients without peripheral atherosclerosis showing that stable atherosclerotic lesions in different vascular districts are inversely related to soluble decoy receptor sRAGE.